The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1073/pnas.1205576109
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and transmissibility of H1N2 influenza virus in ferrets imply the continuing threat of triple-reassortant swine viruses

Abstract: Efficient worldwide swine surveillance for influenza A viruses is urgently needed; the emergence of a novel reassortant pandemic H1N1 (pH1N1) virus in 2009 demonstrated that swine can be the direct source of pandemic influenza and that the pandemic potential of viruses prevalent in swine populations must be monitored. We used the ferret model to assess the pathogenicity and transmissibility of predominant Korean triple-reassortant swine (TRSw) H1N2 and H3N2 influenza viruses genetically related to North Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Although swine influenza viruses only occasionally infect humans and rarely cause pandemics (39), they appear to pose an increasing risk. TRS viruses with human-like HA and NA proteins are airborne-transmissible in ferrets (40,41). Moreover, diverse swine viruses to which humans lack immunity are emerging through reassortment with the pH1N1 viruses (42).…”
Section: Discussionmentioning
confidence: 99%
“…Although swine influenza viruses only occasionally infect humans and rarely cause pandemics (39), they appear to pose an increasing risk. TRS viruses with human-like HA and NA proteins are airborne-transmissible in ferrets (40,41). Moreover, diverse swine viruses to which humans lack immunity are emerging through reassortment with the pH1N1 viruses (42).…”
Section: Discussionmentioning
confidence: 99%
“…Substitution of the isogenic CT-Sw/1204 HA alone or in combination with NA into the closely related Sw/1130 H1N2 virus enhanced replication and pathogenicity in mice, confirming the role of the HA 225G and NA 315N mutations found in CT-Sw/1204 after a single passage in ferrets (10). However, the reciprocal expression of Sw/1130 HA or HA-NA in the background of CT-Sw/1204 could not render the recombinant reassortant virus completely attenuated, implying that the remaining viral segments are required for pathogenicity.…”
Section: Discussionmentioning
confidence: 53%
“…The 50% lethal doses (LD 50 ) of viruses that killed more than 50% of the mice were determined in additional groups of mice that were inoculated intranasally with 10-fold serial dilutions (10 2 to 10 6 TCID 50 /50 l) of virus. Groups of three 14-to 16-week-old female outbred ferrets (Mustela putorius furo; Wuxi Sangosho Pet Park Co., China) that were seronegative for influenza virus exposure/infection by hemagglutination inhibition (HI) and NP enzyme-linked immunosorbent assays (ELISAs) were inoculated intranasally (300 l/nostril) and intratracheally (400 l) with the indicated recombinant virus (10 5.5 TCID 50 /ml) as previously described (10). At 1 day p.i., each inoculated ferret was paired with a seronegative ferret (in a 1:1 setup) in barrier-separated transmission isolators (35 mm apart) that permitted only aerosol contact.…”
Section: Viral Growth Kinetics In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Most reported triple-reassortant swine H1 viruses caused mild disease, were inefficiently transmitted through the air in ferrets (34,35), and had restricted circulation in humans (36), even though they generally possess strong binding affinity for the ␣2,6-linked human-like receptor (37). Our previous (7) and present studies demonstrated that the parental rH1N1 virus had viral characteristics identical to those of these reported triple-reas- sortant viruses.…”
Section: Discussionmentioning
confidence: 74%